Molybdenum, Nickel, Titanium and Vanadium Complexes of Triethylene Tetramine, Diethylene Triamine Based Schiff Bases - Vijayanthimala, R.; Dhanalakshmi, S. (Asian Journal of Chemistry, 2010)
Schiff base complexes of Mo(VI), Ni(II), Ti(IV) and V(V) formed from salicylaldehyde and triethylenetetramine (trien) namely (Ni2+L1).2H2O, [Ti4+(L1H2)(C2O4)2].2H2O, [V5+O2L1H]·2H2O and [Mo6+O2[L1H2)] Mo6+O4 where L1H2 represents the trien Schiff base and Mo(V), Ni(II), Ti(III) and V(V) complexes formed from salicylaldehyde and diethylenetriamine (dien) namely [Ni2+(L2H)2].H2O, [KTi3+(L2H)2C2O4], [V5+O2L2H)] and [Mo5+L2]2 (Mo6+O4)3.2H2O where L2H2 represents the dien Schiff base are reported. The complexes have been characterized by elemental and thermal analysis, conductivity studies, IR, NMR, EPR and UV-VIS studies. Some of the complexes show promising antibacterial activity against bacterial K. pneamonia, E. coli, P. vulgaris, Salmonella typhi, E. faecalis, P. aeruginosa, S. epidermis, methiciline resistant S. aureus, ciprofloxin resistant E. coli and carbapennen resistant A. baumanii.